High performance triboelectric nanogenerators based on phase-inversion piezoelectric membranes of poly(vinylidene fluoride)-zinc stannate (PVDF-ZnSnO3) and polyamide-6 (PA6). (December 2016) - Soin, Navneet; Zhao, Pengfei; Prashanthi, Kovur; Chen, Jinkai; Ding, Peng; Zhou, Erping; Shah, Tahir; Ray, Sekhar C.; Tsonos, Christos; Thundat, Thomas; Siores, Elias; Luo, Jikui
Abstract: Vertical contact-separation mode triboelectric generator (TEG) based on lead-free perovskite, zinc stannate (ZnSnO3 )-polyvinylidene fluoride (PVDF) composite and polyamide-6 (PA6) membrane is demonstrated. For the 5 wt% PVDF-ZnSnO3 nanocomposites, the facile phase-inversion method provides a simple route to achieve high crystallinity and β-phase with a piezoelectric coefficient d33 of −65 pm V −1, as compared to −44 pm V −1 for pristine PVDF membranes. Consequently, at a cyclic excitation impact of 490 N/3 Hz, the PVDF-ZnSnO3 /PA6 based TEGs provide a significantly higher voltage of 520 V and a current density of 2.7 mA m −2 (corresponding charge density of 62.0 µC m −2 ), as compared to the pristine PVDF-PA6 TEG which provides up to 300 V with a current density of 0.91 mA m −2 (corresponding to a charge density of 55.0 µC m −2 ). This increase in the electrical output can be attributed to not only the enhanced polarisation of PVDF by ZnSnO3 leading to an increase in the β-phase content, but also to the surface charge density increase by stress induced polarisation of ZnSnO3, leading to the generation of stronger piezoelectric potential. The work thus introduces a novel method of enhancing the surface charge density via the addition of suitable high polarisation piezoelectric materials thus eliminating the need for prior charge injection for fluoropolymer membranes. Graphical abstract: Highlights: Contact-mode TEGs prepared using phase-inversion PVDF-ZnSnO3 & PA6 membranes. At 490 N/3 Hz, PVDF-ZnSnO3 TEG provides 520 V/2.7 mA m −2 vs. 300 V/0.9 mA m −2 for PVDF/PA6 TEG. For PVDF-ZnSnO3 d33 of −65 pm V −1 provides higher charge-density & piezo-potential. Phase-inversion with high polarisation material eliminates prior charge injection need.